L-arginine stimulates fibroblast proliferation through the GPRC6A-ERK1/2 and PI3K/Akt pathway. - Takashi Fujiwara; Shigeyuki Kanazawa; Ryoko Ichibori; Tomoko Tanigawa; Takuya Magome; Kenta Shingaki; Shingo Miyata; Masaya Tohyama; Ko Hosokawa (PLoS ONE, 2014)
L-arginine is considered a conditionally essential amino acid and has been shown to enhance wound healing. However, the molecular mechanisms through which arginine stimulates cutaneous wound repair remain unknown. Here, we evaluated the effects of arginine supplementation on fibroblast proliferation, which is a key process required for new tissue formation. We also sought to elucidate the signaling pathways involved in mediating the effects of arginine on fibroblasts by evaluation of extracellular signal-related kinase (ERK) 1/2 activation, which is important for cell growth, survival, and differentiation. Our data demonstrated that addition of 6 mM arginine significantly enhanced fibroblast proliferation, while arginine deprivation increased apoptosis, as observed by enhanced DNA fragmentation. In vitro kinase assays demonstrated that arginine supplementation activated ERK1/2, Akt, PKA and its downstream target, cAMP response element binding protein (CREB). Moreover, knockdown of GPRC6A using siRNA blocked fibroblast proliferation and decreased phosphorylation of ERK1/2, Akt and CREB. The present experiments demonstrated a critical role for the GPRC6A-ERK1/2 and PI3K/Akt signaling pathway in arginine-mediated fibroblast survival. Our findings provide novel mechanistic insights into the positive effects of arginine on wound healing.